2009
DOI: 10.1542/peds.2008-2536
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Correct Depth of Chest Compression for Infants and Children? A Radiological Study

Abstract: Radiological assessment of infants' and children's chests indicates similar or higher compression depths for infants and children versus the recommended compression depths for adults (3.8-5.1 cm) according to current guidelines. More evidence is needed to guide the proper depth of chest compression in pediatric populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 31 publications
3
25
0
Order By: Relevance
“…While the Guidelines are developed using a rigorous evidence evaluation process, 36 little data has been collected from young children in cardiac arrest. As an example, in the most recent Guideline revision, using CT 37,38 and anthropometric data 17 collected from healthy children, expert consensus decided that the real “risk” to the child is for providers to not push hard enough, so the recommended depth for children was increased, even though there was little evidence to suggest that we could achieve such depths. The current Guidelines, which recommend the same CC depth targets for 1 year olds and adults, may need to be re-evaluated, particularly when the average mattress compensated CC depth achieved in the IDE cohort was only 28mm.…”
Section: Discussionmentioning
confidence: 99%
“…While the Guidelines are developed using a rigorous evidence evaluation process, 36 little data has been collected from young children in cardiac arrest. As an example, in the most recent Guideline revision, using CT 37,38 and anthropometric data 17 collected from healthy children, expert consensus decided that the real “risk” to the child is for providers to not push hard enough, so the recommended depth for children was increased, even though there was little evidence to suggest that we could achieve such depths. The current Guidelines, which recommend the same CC depth targets for 1 year olds and adults, may need to be re-evaluated, particularly when the average mattress compensated CC depth achieved in the IDE cohort was only 28mm.…”
Section: Discussionmentioning
confidence: 99%
“…in children during pediatric resuscitation. The chest compression depth was expressed as both a fraction of the depth of the chest and an absolute measurement [14,15]. However, in the 2010 guideline of adult resuscitation, it was expressed as only an absolute measurement, without a fraction of the depth of the chest.…”
Section: Discussionmentioning
confidence: 99%
“…However, not much attention has been paid on the proper hand position for paediatric CPR. Kao et al 27 used CT and briefly reported that the most commonly observed anatomical structure beneath the compression landmarks was the heart in 92.1-100% of the children, but they did not specify which parts of the heart are compressed. CT images can show the objective spatial relationship between the surface landmarks on the chest and the internal organs underneath them.…”
Section: Introductionmentioning
confidence: 99%